2019
DOI: 10.4149/neo_2018_180606n377
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOXB-AS1 promotes proliferation, migration and invasion of glioblastoma cells via HOXB-AS1/miR-885-3p/HOXB2 axis

Abstract: Long non-coding RNAs (lncRNAs) have been proven to play important roles in carcinogenesis and development of numerous cancers, but their biological functions in glioblastoma remain largely unknown. In this study, we found that HOXB-AS1 was highly expressed in human glioblastoma tissues and cell lines, and was associated with survival time of patients. Further analysis showed that knock-down of HOXB-AS1 inhibited cell proliferation via inducing S phase cell cycle arrest and suppressed migration and invasion abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…15 Moreover, miR-885-3p acted as a tumor suppressor in glioblastoma and gastric cancer. 16,17 Our studies showed that miR-885-3p was down-regulated in PBMCs from T1D patients, which was consistent with recent findings from Zuraek et al. 10 Consistently, our results indicated that miR-885-3p had inhibitory actions on the immune response of THP-1 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15 Moreover, miR-885-3p acted as a tumor suppressor in glioblastoma and gastric cancer. 16,17 Our studies showed that miR-885-3p was down-regulated in PBMCs from T1D patients, which was consistent with recent findings from Zuraek et al. 10 Consistently, our results indicated that miR-885-3p had inhibitory actions on the immune response of THP-1 cells.…”
Section: Discussionsupporting
confidence: 92%
“…12 MiR-885-3p could target γ-synuclein 3'-UTR and repress γ-synuclein, which may be involved in the tumor metastasis. 16,17 Our studies showed that miR-885-3p was down-regulated in PBMCs from T1D patients, which was consistent with recent findings from Zuraek et al. 14 MiR-885-3p could target the 3'-UTR of vitamin D receptor and contributed to the development of pressure ulcers.…”
Section: Tlr4 Was Directly Targeted By Mir-885-3psupporting
confidence: 91%
“…24,25 Moreover, lncRNA HOXB-AS1 promoted proliferation, migration and invasion of glioblastoma cells via miR-885-3p/HOXB2 axis. 16 It has also been reported that lncRNA RGMB-AS1 promoted glioma growth and invasion through miR-1200/HOXB2 axis. 26 In the present study, LINC00662 also facilitated ESCC progression by regulating miR-340-5p/HOXB2 axis.…”
Section: Discussionmentioning
confidence: 97%
“…13,14 In addition, miR-4324 has been found to function as a tumor suppressor in colorectal cancer by targeting HOXB2, 15 and lncRNA HOXB-AS1 promoted proliferation, migration and invasion of glioblastoma cells via miR-885-3p/HOXB2 axis. 16 Moreover, HOXB2 has been demonstrated to be a target of miR-340 in acute myeloid leukemia. 17 However, the role of HOXB2 in ESCC has not been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was latterly found that HOXB‐AS1 played a tumor‐promoting role in GBM (Chen et al, 2019). The present study purposed to inspect more sophisticated mechanism underlying HOXB‐AS1 in GBM.…”
Section: Discussionmentioning
confidence: 99%